2022
DOI: 10.18231/j.ijn.2021.052
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of multi-site micro recordings of subthalamic nucleus neurons using machine learning MER with DBS in Parkinson`s – A simulation study

Abstract: Multineural spikes were acquired with a multisite electrode placed in the hippocampus pyramidal cell layer of non-primate anesthetized snitch animals. If the impedance of each electrode-site is relatively low and the distance amongst electrode sites is appropriately miniatured, a spike generated by a neuron is parallelly recorded at multielectrode sites with different amplitudes. The covariance between the spike of the at each electrode-point and a template was computed as a damping-factor due to the volume co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…[3] The uniqueness of diabetic striatopathy is that it is usually self-limiting with prompt management of the hyperglycemia. It occurs in non ketotic hyperglycemic hyperosmolar state (HHS) [4,5], uncommon with Diabetic Ketoacidosis (DKA) and rare without DKA [6] Hyperintense signal in contralateral (to the side of the abnormal movements) putamen on T1-WI without surrounding edema or mass effect, along with hyperglycemia and choreiform movements, is pathognomonic of DS [7,8]. The patient was started on Tetrabenazine 25mg BD for 15 days,however she did not reposnd to the same and was then started on Haloperidol 0.5mg HS with an advise to follow up after 1 month.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[3] The uniqueness of diabetic striatopathy is that it is usually self-limiting with prompt management of the hyperglycemia. It occurs in non ketotic hyperglycemic hyperosmolar state (HHS) [4,5], uncommon with Diabetic Ketoacidosis (DKA) and rare without DKA [6] Hyperintense signal in contralateral (to the side of the abnormal movements) putamen on T1-WI without surrounding edema or mass effect, along with hyperglycemia and choreiform movements, is pathognomonic of DS [7,8]. The patient was started on Tetrabenazine 25mg BD for 15 days,however she did not reposnd to the same and was then started on Haloperidol 0.5mg HS with an advise to follow up after 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…Background: Hyperreflexia is often seen in PD 1 and muscle strength is diminished 2 . Various studies have suggested the relationship between the muscles and cognitive functions [3][4][5][6][7] . How it affects cognitive performance is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The STN-DBS was developed as a basic corrective option, is an active therapy for patients with Parkinson's disease (PD) 1 when PD motor symptoms such as tremor, rigidity, and Bradykinesia, and postural instability are not preventive by the medication. 2 However, its success is impeded by limited and some degree of knowledge of restorative mechanisms and the lack of a robust feedback signal for tailoring induced stimulations. The fundamental outcomes of the induced stimuli are for the progress of these key objective motor symptoms.…”
Section: Introductionmentioning
confidence: 99%